Introducing ductility in hybrid carbon fibre/self-reinforced composites through control of the damage mechanisms. (1st November 2015) - Swolfs, Yentl; Meerten, Yannick; Hine, Peter; Ward, Ian; Verpoest, Ignaas; Gorbatikh, Larissa
Abstract: Carbon fibre composites possess excellent mechanical properties, but suffer from brittleness. Hybridisation with self-reinforced polypropylene (SRPP) is a promising strategy to introduce ductility into carbon fibre-reinforced polypropylene (CFRPP). The present work demonstrates how different damage mechanisms in these hybrid composites change as a function of the carbon fibre volume fraction, the directionality of CFRPP and SRPP and their relative layer thickness. Multiple fractures of the CFRPP layers or "fragmentation" is achieved by optimising these parameters. This leads to a ductile hybrid composite with a gradual failure development.